2010
DOI: 10.1155/2010/459862
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Oestrogens, Antioestrogens and SERMs on Pancreatic Solid Pseudopapillary Neoplasm-Derived Primary Cell Culture

Abstract: Background: Solid-pseudopapillary neoplasms of the pancreas (SPNs) are uncommon tumours usually frequent in young women. Although the pathogenesis of SPNs is uncertain a potential influence of the sex hormone milieu on the biology of these tumours has been suggested. The controversial expression of oestrogen receptors (ERs) in SPNs, provide a rationale for studying the effects of oestrogenic molecules on SPN development.Methods: The expression of a large series of hormonal ligands and receptors was evaluated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…For estrogen, Tognarini I et al demonstrated the strong expression of ER in tumor tissue and the proliferative action of estrogen in vitro, offering potential treatment strategies for SPN via selective ER modulators. 27 Similarly, another study reported that antiestrogen drugs for cases with unresectable liver metastasis resulted in a favorable prognosis. 28 Therefore, in our study, we presumed that the early onset in women might be attributed to exposure to progesterone and/or estrogen during the reproductive period, while the late onset might be attributed to accumulated lifetime environmental exposure.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For estrogen, Tognarini I et al demonstrated the strong expression of ER in tumor tissue and the proliferative action of estrogen in vitro, offering potential treatment strategies for SPN via selective ER modulators. 27 Similarly, another study reported that antiestrogen drugs for cases with unresectable liver metastasis resulted in a favorable prognosis. 28 Therefore, in our study, we presumed that the early onset in women might be attributed to exposure to progesterone and/or estrogen during the reproductive period, while the late onset might be attributed to accumulated lifetime environmental exposure.…”
Section: Discussionmentioning
confidence: 95%
“…Case reports showed that SPN grew rapidly during pregnancy, 24‐26 and progesterone might act as an oncogenic factor in SPN. For estrogen, Tognarini I et al demonstrated the strong expression of ER in tumor tissue and the proliferative action of estrogen in vitro, offering potential treatment strategies for SPN via selective ER modulators 27 . Similarly, another study reported that antiestrogen drugs for cases with unresectable liver metastasis resulted in a favorable prognosis 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the estrogen receptor was strongly expressed in tumor tissues. The proliferative action of estrogen in vitro was also identified (32). Therefore, the sex features of SPN may be due to exposure to progesterone and/or estrogen during the reproductive period in females (7).…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that SPTs have relations to female sex hormones. Supporting this hypothesis, the study of Isabella Tognarini et al concluded that estrogenderived molecules could affect the development of SPT cells [7].…”
Section: There Were 33 Cases With the Histopathological Resultsmentioning
confidence: 90%